Increased Cerebral Vascular Reactivity in the Tau Expressing rTg4510 Mouse: Evidence against the Role of Tau Pathology to Impair Vascular Health in Alzheimer's Disease. Issue 3 (March 2015) - Wells, Jack A; Holmes, Holly E; O'Callaghan, James M; Colgan, Niall; Ismail, Ozama; Fisher, Elizabeth MC; Siow, Bernard; Murray, Tracey K; Schwarz, Adam J; O'Neill, Michael J; Collins, Emily C; Lythgoe, Mark F
Vascular abnormalities are a key feature of Alzheimer's disease (AD). Imaging of cerebral vascular reactivity (CVR) is a powerful tool to investigate vascular health in clinical populations although the cause of reduced CVR in AD patients is not fully understood. We investigated the specific role of tau pathology in CVR derangement in AD using the rTg4510 mouse model. We observed an increase in CVR in cortical regions with tau pathology. These data suggest that tau pathology alone does not produce the clinically observed decreases in CVR and implicates amyloid pathology as the dominant etiology of impaired CVR in AD patients.